An Enhanced Piezoelectric Vibration Energy Harvesting System with Macro Fiber Composite - Shuwen Zhang; Bo Yan; Yajun Luo; Weikai Miao; Minglong Xu (Shock and Vibration)
Self-power supply is a promising project in various applied conditions. Among this research area, piezoelectric material-based energy harvesting (EH) method has been researched in recent years due to its advantages. With the limitation of energy form acceptance range of EH circuit system, a sum of energy is not accessible to be obtained. To enlarge the EH quantity from the vibration, an enhanced piezoelectric vibration EH structure with piezoelectric film is developed in this work. Piezoelectric-based energy harvesting mechanism is primarily proposed in this work. The special-designed electric circuit for EH from macro fiber composite (MFC) is proposed and then analyzed. When the structure vibrates in its modes of frequencies, the experiments are developed to measure the EH effect. The energy harvested from the vibrating structure is analyzed and the enhanced effect is presented. The results indicate that, with the enhanced EH structure in this work, vibration energy from structure is obtained in a larger range, and the general EH quantity is enlarged.